The quantitative profiling of blood mSEPT9 determines the detection performance on colorectal tumors. (14th November 2018) - Song, Lele; Wang, Jiayu; Wang, Huaiqing; Chen, Yan; Jia, Jia; Guo, Shaohua; Liu, Hongyi; Peng, Xiumei; Xiao, Wenhua; Gong, Yuan; Yang, Bo; Lu, Yinying; et al.
Aim: To investigate the quantitative relationship between the positive detection rate (PDR) in colorectal tumor detection and the mSEPT9 level.Materials & methods: The level of blood mSEPT9 in various colorectal diseases was quantified by the Epi proColon 2.0 assay. ΔΔCt values were calculated representing the mSEPT9 level. A total of 1347 subjects were recruited in this quantitative study.Results: PDR or sensitivity was positively correlated with the progression of colorectal tumors and the mSEPT9 level in an exponential relationship. The mSEPT9 level of CRC exhibited a distinct pattern of distribution. Strong correlation was found between mSEPT9 level and PDR or sensitivity in various tumor differentiation, pathological types or metastasis.Conclusion: The quantitative profiling of blood mSEPT9 determines the detection performance on colorectal tumors.